Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)

Comité des usagers JHSB : Mandat 2018-2021 - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Programme des soins palliatifs et de fin de vie - Jeffery Hale - Saint Brigid's (JHSB) (2015)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Consultation publique sur les conditions de vie des aînes : Un enjeu de société, une responsabilité qui nous interpelle tous - Conseil catholique d'expression anglaise (2007)
Le Conseil catholique d’expression anglaise aimerait féliciter le gouvernement du Québec pour avoir reconnu l’importance des problèmes affectant les aînés et notre population vieillissante et pour avoir créé le poste de ministre responsable des Aînés. Nous accueillons avec plaisir l’initiative de Mme Marguerite Blais, ministre responsable des Aînés, de tenir des audiences publiques sur les conditions de vie des aînés au Québec. Cet enjeu constitue une grande source de préoccupations pour notre communauté et pour ses institutions au service des personnes âgées, dont l’expérience dans ce domaine est considérable.

Choices through Knowledge: Community training in palliative care - Jones, Jo-Ann; Quebec Association for Adult Learning (QAAL) (2004)

Executive Summary : The English Speaking Catholic Council’s Response to Public Consultation on Seniors’ Living Conditions - The English Speaking Catholic Council (ESCC)
For the English Speaking Catholic Council (ESCC), the care of seniors, especially the frail elderly, is a moral and social imperative for us all. Our community has created a number of specialized institutions and services over the past one hundred and fifty years that allow us to carry out our responsibilities to seniors, but Quebec faces many challenges if we want to protect and promote fully the interests of older citizens.